Building resilience of livelihood systems to disaster: Lessons learned from the tsunami disaster recovery process - Wardah Hasyim (Proceedings of AICS - Social Sciences, 2013)
This research aimed to assess the contribution of livelihood recovery efforts, including communities’ own initiatives and external support, to people’s livelihoods in the tsunami-affected areas in Aceh Province, Indonesia. Using a mixed-methods approach and covering fourteen tsunami-affected villages located in Pidie and Aceh Besar district, the study adopts the concept of Sustainable Livelihoods and modifies the Sustainable Livelihoods Framework (SLF) for its critical analysis. The findings show that people’s strategies were influenced by local values, practices and institutions, previous hardships, and contributions from different livelihoods recovery programmes implemented by relief and development agencies. In dealing with the impacts of the tsunami, men and women in the affected communities showed various short-term responses or coping strategies. For longer term recovery, communities developed adaptation and transformation strategies for their livelihood activities. In many cases, people adjusted existing livelihood activities to the changes as well as developing new livelihood strategies. This led to different outcomes for households, either being more resilient or more vulnerable, as well as influencing their future access to assets.Keywords: Disaster, Livelihoods, Resilience, and Sustainable Livelihoods.